Regionalism and culinary centralism in a 19th century Huancayo manuscript: influences and flavors - Zapata Acha, Sergio (2019)
The study of cookbooks is of the greatest importance to understand the evolution of a cuisine. In Peru, the recipes published in the 19th century are scarce. With more than 300 recipes, the manuscript Copia de comidas para el uso de la señorita Isabel Gertrudis Alfaro, dated in Huancayo in 1897, is significant because it presents a wide selection of recipes that includes appetizers, soups, main dishes, desserts and drinks; among which about twenty Andean foods are original, and whose coding is documented for the first time. The objective of this study is to show, through registration, the influence of the dominant Lima culinary centralism in an important Andean region; in addition, to expose the existence of regional mestizo foods with native and Hispanic contributions, as well as, the influence of Italian foods, product of the immigration process registered mainly in the second half of the 19th century..